Optimization of Fenton’s Process for the Treatment of Cotton Textile Wastewater using Response Surface Methodology - Parashuram Mulgund, Sangeetha; Kalburgi, P.B.; Rakaraddi, P.G. (Asian Journal of Chemistry, 2020)
Degradation of cotton textile wastewater using Fenton’s process was investigated. The effect of individual and interactive operating parameters on the response was analyzed using central composite design (CCD), a commonly used form of response surface methodology (RSM). The operating parameters selected were pH, dosage of hydrogen peroxide, dosage of iron and the responses (dependent parameters) were chemical oxygen demand (COD) and colour. The model derived correlation coefficients R2 and R2 adj for COD were 0.982 and 0.966, respectively and the values were almost similar for colour also. The optimum values for various operating parameters namely pH, H2O2 and Fe2+ dosage were found to be 3.33, 60.57 and 1.56 mM, respectively for electrolysis time of 60 min. By performing the experiments with these values of operating parameters, the COD and colour removal efficiencies were found to be 83.5% and 98.1%, respectively.